Kajian Urgensi Public Private Partnerships di Kota Bandung - Mary Ismowati (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
Bandung city government's desire to work on various projects with a mechanism of Public Private Partnerships ( PPP ) due to limitations of the government for the city of Bandung well within the capability of funding, human resources , technological capabilities , and so forth . This is done to help realize the